P-type β-gallium oxide: A new perspective for power and optoelectronic devices - Mike Jennings (Materials Today Physics, 2017)
Wide-bandgap semiconductors (WBG) are expected to be applied to solid-state lighting and power devices, supporting a future energy-saving society. Here we present evidence of p-type conduction in the undoped WBG β-Ga2O3. Hole conduction, established by Hall and Seebeck measurements, is consistent with findings from photoemission and cathodoluminescence spectroscopies. The ionization energy of the acceptor level was measured to be 1.1eV above the valence band edge. The gallium vacancy was identified as a possible acceptor candidate based on thermodynamic equilibrium Ga2O3 (crystal) – O2 (gas) system calculations (Kroger theory) which revealed a window without oxygen vacancy compensation. The possibility of fabricating large diameter wafers of β-Ga2O3 of p and n type nature, provides new avenues for high power and deep UV-optoelectronic devices.